Home and away: personal autonomy limitation in the liminal work context of fly-in-fly-out camps and psychological distress - Fruhen, L.S.; Parker, Sharon (2024)
Fly-in-fly-out (FIFO) camps are liminal work environments in which work and personal life are blended. In such context, an important characteristic is the limitation to one’s freedom to carry out actions that usually occur outside of work contexts (e.g., choosing when to eat dinner), which we refer to as ‘personal autonomy limitation’. The role of personal autonomy limitation for FIFO workers’ mental health has not been systematically investigated at a larger scale. We test whether personal autonomy limitation predicts workers’ psychological distress and their psychological work detachment while they are at their residential home. We also investigate the moderating role of roster ratios (i.e., the ratio of days workers spend on site and at home) on these hypothesized associations. Online survey data from 1547 Australian resources sector FIFO workers showed that higher levels of perceived personal autonomy limitation in FIFO camps predicted greater psychological distress, with this effect partially mediated by lower detachment from work whilst at home. Roster ratio did not moderate the direct or mediated relationships between personal autonomy limitation in FIFO camps and worker psychological distress. The findings identify personal autonomy limitation as a work design characteristic that is relevant to FIFO and other workers’ mental health.